GAMBARAN HISTOPATOLOGI HATI TIKUS WISTAR YANG DIBERIKAN BORAKS - Tatukude, Rico Lukas; Loho, Lily; Lintong, Poppy M. (Universitas Sam Ratulangi, 2014)
Abstract: Borax is an ingredient that is widely used for industrial or antiseptic cleaning agents that are toxic, but borax is used as an additive ind foods and any experience accumulated in the liver that can cause liver disfumction. Methods: The aim of research is to see macroscopic and microscopic of live wistar rats were given different doses of borax. Rats were used as much as 10 animals were divided into 4 groups. The control group (K1) 1 rat, K2 ( borax 20mg), K3 (borax 30 mg), K4 (borax 40 mg) each of 3 rats by administration for 1,5 and 10 days. Result: The result showed the rats had grossly enlarged liver size, liver weight gain and blackish brown in the group given 40 mg of borax and microscopically, the cells were exposed to borax liver showed hydropic degeneration, proliferation fibrolas and fibrosis. From this study it can be concluded that the administraion of borax 20mg, 30mg, 40mg for 10 days caused fatty liver and mild fibrosis. Keywords: Borax, Liver Disfunction. Abstrak: Latar Belakang: Boraks merupakan bahan industri yang banyak digunakan untuk antiseptik atau zat pembersih. Akan tetapi boraks juga masih digunakan sebagai bahan tambahan pada makanan dan dapat memberikan efek karsinogenik dan disfungsi hati. Metode: Penelitian ini bertujuan untuk melihat gambaran histopatologi hati tikus wistar yang diberi boraks. Tikus yang digunakan sebanyak 10 ekor. Kelompok kontrol (K1) sebanyak 1 ekor tikus, K2, K3, K4 masing-masing 3 ekor tikus yang diberikan dosis 20mg, 30mg, dan 40mg yang diterminasi pada hari ke 1,5, dan 10. Hasil: Dari hasil penelitian menunjukkan secara mikroskopik sel hati yang terpapar boraks mengalami degenerasi hidropik, proliferasi fibrolas, dan secara makroskopis sel hati hewan coba mengalami perbesaran dan berwarna coklat kehitaman. Pemberian boraks 20mg, 30mg, dan 40mg dapat menyebabkan kerusakan hati. Kata Kunci: Boraks, Disfungsi Hati.